2013
DOI: 10.1007/s00405-013-2355-x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal maxillary cysts: long-term subjective outcomes after surgical treatment

Abstract: Mucosal maxillary cysts (MMCs) are usually asymptomatic and are often diagnosed as an incidental finding. The aim of this study is to assess clinical significance of MMCs and the long-term effect of surgical treatment on the symptoms initially addressed to MMCs. The study included a retrospective analysis of 64 patients who had undergone surgery for MMC using a questionnaire focused mainly on the effect surgery had on symptoms. Mean time of follow-up was 79 months. Patients were also divided and compared accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…APs are solitary, dome -shaped radiopaque masses located on the maxillary sinus floor that can further reduce the size of this anatomical structure. [11][12][13][25][26][27] This finding is consistent with the present case since a veiling of the maxillary sinus caused by the AP was observed, and the central radiopaque area in the maxillary sinus led us to hypothesize a diagnosis of COC for the lesion in the antrum (rather than the periapical one).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…APs are solitary, dome -shaped radiopaque masses located on the maxillary sinus floor that can further reduce the size of this anatomical structure. [11][12][13][25][26][27] This finding is consistent with the present case since a veiling of the maxillary sinus caused by the AP was observed, and the central radiopaque area in the maxillary sinus led us to hypothesize a diagnosis of COC for the lesion in the antrum (rather than the periapical one).…”
Section: Discussionsupporting
confidence: 90%
“…Surgical excision in these cases is unnecessary, as studies have shown no progression or even regression during follow -up. 11,12,25 When present, symptoms range from headaches to face pain and nasal obstruction and discharge. 12,25 In some cases, a positive aspiration mimicking a cystic lesion may be present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mucous retention cyst (mucocele) of the maxillary sinus is a phenomenon resulting from the retention of mucous present in the mucous glands of the maxillary sinus lining epithelium, being detected as a radiographic finding in the dental examinations by image [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%